L’HÔPITAL’S RULES AND THEIR APPLICATION IN CALCULATING LIMITS - Boboqulova Durdona Sanjar qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: L’Hôpital’s Rule is a powerful method in calculus used to evaluate limits that result in indeterminate forms such as 0/0 or ∞/∞. This article provides a formal explanation of the rule, its conditions of use, and illustrates its application through various examples. By simplifying complex limits, L’Hôpital’s Rule serves as a key analytical tool in both theoretical mathematics and applied fields like physics, economics, and engineering.